2019
DOI: 10.1097/sla.0000000000002660
|View full text |Cite
|
Sign up to set email alerts
|

The Systemic-immune-inflammation Index Independently Predicts Survival and Recurrence in Resectable Pancreatic Cancer and its Prognostic Value Depends on Bilirubin Levels

Abstract: SIII is an independent predictor of cancer-specific survival and recurrence in patients with resectable PDAC. SIII may lose its prognostic significance in patients with high bilirubin levels. Properly designed prospective studies are needed to further confirm this hypothesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
185
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 212 publications
(206 citation statements)
references
References 46 publications
11
185
1
Order By: Relevance
“…Furthermore, almost all of the SIR markers were significantly correlated with poorer prognosis of DFS in patients with curatively resected CRC (log‐rank test, CRP: P = .0009, serum albumin level: P = .004, NLR: P = .005, PLR: P = .025, SII: P < .0001, LMR: P = .025, NPS: P = .29, and PNI: P = .0006, respectively; Figure S1I–P). Collectively, these findings validated the prognostic impact of SIR markers using optimal cutoff values of these markers established from previous evidence in patients with CRC …”
Section: Resultssupporting
confidence: 70%
See 1 more Smart Citation
“…Furthermore, almost all of the SIR markers were significantly correlated with poorer prognosis of DFS in patients with curatively resected CRC (log‐rank test, CRP: P = .0009, serum albumin level: P = .004, NLR: P = .005, PLR: P = .025, SII: P < .0001, LMR: P = .025, NPS: P = .29, and PNI: P = .0006, respectively; Figure S1I–P). Collectively, these findings validated the prognostic impact of SIR markers using optimal cutoff values of these markers established from previous evidence in patients with CRC …”
Section: Resultssupporting
confidence: 70%
“…NPS was calculated as follows: patients with a neutrophil count ≤7 × 10 3 /μL and a platelet count ≤40 × 10 4 /μL scored 0, patients with a neutrophil count >7 × 10 3 /μL or a platelet count of >40 × 10 4 /μL scored 1, and patients with a neutrophil count >7 × 10 3 /μL and a platelet count >40 × 10 4 /μL scored 2, as previously described . The cutoff value of each marker was defined as 0.5 mg/dL, 3.5 g/dL, 3, 150, 900, 3, 45, and score 1 or 2, respectively, based on previous evidence.…”
Section: Methodsmentioning
confidence: 99%
“…(Glasgow Prognostic Score and CA19.9) showed reasonable performance. Recently, the systemic inflammation index has shown to be an independent predictor of cancer‐specific survival and recurrence in resectable pancreatic cancer. As immunotherapy holds promise as treatment for pancreatic cancer, systemic inflammatory scores could assist in patient selection in future.…”
Section: Discussionmentioning
confidence: 99%
“…It is an index that incorporates the absolute blood counts of neutrophils, lymphocytes as well as platelets, by multiplying the platelet count by the ratio of neutrophil and lymphocyte counts. Several studies found that the SII is a prognostic factor in patients with solid cancers, such as hepatocellular carcinoma, colorectal and pancreatic cancer . So far, it is unknown whether an increased SII also is a marker for developing incident cancer in healthy individuals.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies found that the SII is a prognostic factor in patients with solid cancers, such as hepatocellular carcinoma, colorectal and pancreatic cancer. [12][13][14] So far, it is unknown whether an increased SII also is a marker for developing incident cancer in healthy individuals.…”
Section: Introductionmentioning
confidence: 99%